Hierarchically structured lithium titanate for ultrafast charging in long-life high capacity batteries - Mateusz Odziomek (Nature Portfolio, 2017)
Both electronic and ionic transport must be optimized in Li4Ti5O12for its use in Li-ion batteries, most promisingly against high voltage cathodes. Here authors synthesize hierarchical porous micrometre-scale structures composed of primary nanoparticles to demonstrate an attractive combination of rate performance, capacity and cycling stability.